Carencia de micronutrientes en rumiantes. Suplementación alternativa mediante el enriquecimiento de forrajes - Ramos, María Laura (2017)
The population growth and the increasing demand of animal source foods have contributed to the intensification of cattle production systems. The use of cattle manure as fertilizer in agricultural soils is an important source of metals, mainly due to the added in high rates of core mineral in animal feed in confined production systems, have resulted in corresponding rise of trace elements in manure. In cattle grazing systems, the natural sources of minerals include forage and water. Therefore, the use of organic amendments rich in trace elements for the forage employed in animal nutrition is an alternative to the mineral supplementation by intravenous injection.\nThe main goal of this PhD Thesis was to evaluate the enrichment of forages with micronutrients by means of organic amendment and the corresponding absorption by ruminants. The results of the present study are presented in several chapters:a) Micronutrients in cattle manure coming from intensive production systems. In this Chapter, the evolution of the cattle industry towards the intensification of production systems was evaluated. In addition, the general characteristics of the intensive production systems and its effect on the composition of the manure were analysed, with special focus on the total content and bioavailability of micronutrients (Cu, Zn, Co and Mo).\nb) Micronutrients deficiency in extensive livestock production systems. In this Chapter the relevant sources of mineral deficiency were reviewed and some common deficiency cases in our country were described. Moreover, the total content and availability of micronutrients (Cu, Zn, Co, Mo and Se) were determined in soils corresponding to areas with mineral deficiency from Buenos Aires province.\nc) Forage enrichment with micronutrients: experience in plant pot and plot. In this Chapter the results from sowing tests were presented. In these tests, excrement coming from intensive production systems containing high concentration of micronutrients (Cu and Zn) was employed as organic amendment.d) Micronutrient metabolism in ruminants. In this Chapter, the release of minerals (Cu and Zn) in the rumen was evaluated by employing different forage mixtures with and without micronutrients fertilization.\nThe obtained results in the different tests conducted during this study led to the following conclusions:\n- The cattle manure coming from intensive production systems presented high total content of Cu and Zn related with the feed consumed by livestock. The sequential extraction for the speciation of these trace metals revealed a higher percentage of the soluble or exchangeable fractions compared with excrement obtained from extensive production systems without the use of mineral supplements.\n- The soil samples analysed presented Cu, Zn and Se concentration close to the lower limit of the normal range for agricultural land. The aforementioned samples were obtained from the Pampa area where a deficiency of such metals was reported. In addition, the sequential extraction showed that these soil samples contained low concentration of bioavailable Cu, Co and Mo whereas the concentration of bioavailable Zn changed significantly among the different samples measured.- The fertilization in plant pot showed positive results from the addition of cattle manure as organic amendments. An increase in the percentage of dry matter and an improvement in the growing parameters of the forage species employed were observed (Lolium Perenne and Trifolium Repens).- The addition of intensive cattle manure led to an increase in Cu and Zn concentration in the foliar biomass of the forage species analysed after 30 days from the sowing time. The increased uptake is favoured by the higher total content and the higher percentage of soluble fraction of such trace metals, provided by the excrement addition.- The results obtained in the fertilization tests showed the enrichment in Cu and Zn in the forages treated with excrement from intensive systems after 30 days from the sowing.\n- Besides, the response to the fertilization with organic amendments was better compared with the use of inorganic fertilizers (CuSO4 ? ZnSO4), regardless of the employed dosage.\n- The use of cattle manure coming from intensive production systems as fertilizers promoted the mobility and gradual release of trace elements from lower bioavailable fractions for plants (such as the fraction of metal complexed to organic matter or the inorganic fraction) obtained by sequential extraction.\n- The addition strategy, doses and persistence in the soils of CuSO4 and ZnSO4 are variables that influenced the incorporation of trace metals in the forages.\n- The forage samples obtained in the tests conducted in plots30 days after the different fertilizer treatments presented a concentration of Cu and Zn that would be adequate to cover the metal trace requirements in beef cattle. However, other variables concerning the animal and the diet should be considered.- Later sowing times (90 days after the treatment) showed variable results to the addition of organic amendments and inorganic fertilization.\n- The lower concentration of Cu and Zn in the foliar biomass measured at later sowing times for all the different fertilization treatments could be explained by the growing dynamics of the forage species, the aging of plant tissues and defoliation process.- The ruminal incubation of fresh forages (enriched with CuSO4 and ZnSO4 and without fertilization) showed high percentages of total dry matter degradability and high release percentages of Cu and Zn into the rumen at short incubation times (3 ? 9 h). Drying of the forage samples in an oven led to\na decrease in the dry matter degradability modifying the subsequent bioavailability of the nutrients.The use of cattle manure coming from intensive production systems as fertilizer contributed the uptake of Cu and Zn in forage species mainly due to the higher concentration and the higher content of bioavailable fractions of such trace metals in soils. Therefore, the use of those organic amendments reduces the risk of environmental pollution due to the excess of micronutrients. In addition, Cu and Zn deficiencies could be balanced in different cattle production areas. The micronutrients contribution to forage can supply the required minerals for cattle production, favoured by the high level of trace elements release in the rumen.